2019
DOI: 10.1101/536052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mouse Norovirus infection arrests host cell translation uncoupled from the stress granule-PKR-eIF2α axis

Abstract: 1 8 1 9 ¶ These authors contributed equally to this work. SF and TEA are Joint Authors 2 0 2 1 Abstract 2 5The integrated stress response (ISR) is a cellular response system activated upon different 2 6 types of stresses, including viral infection, to restore cellular homeostasis. However, many viruses 2 7 manipulate this response for their own advantage. In this study we investigated the association 2 8between murine norovirus (MNV) infection and the ISR and demonstrate that MNV regulates the 2 9ISR by activa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Recent work confirms that the preferential viral translation is not driven by the GCN2-mediated phosphorylation of eIF2α in MNV infected cells (Brocard et al, 2018). We note however that others have suggested that NS3 may contribute to the translational shut off seen in MNV infected cells (Fritzlar et al, 2019), with the caveat that this observation was made outside of the context of infected cells and used overexpressed tagged viral proteins. We suspect that noroviruses use multiple mechanisms that work cooperatively to enable the control of host gene expression and the subsequent translation of the cellular mRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work confirms that the preferential viral translation is not driven by the GCN2-mediated phosphorylation of eIF2α in MNV infected cells (Brocard et al, 2018). We note however that others have suggested that NS3 may contribute to the translational shut off seen in MNV infected cells (Fritzlar et al, 2019), with the caveat that this observation was made outside of the context of infected cells and used overexpressed tagged viral proteins. We suspect that noroviruses use multiple mechanisms that work cooperatively to enable the control of host gene expression and the subsequent translation of the cellular mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…While our data fit with a primary role for G3BP1 in norovirus translation, we are unable to exclude the possibility that G3BP1 plays other roles in the viral life cycle. Recent studies have confirmed that G3BP1 is enriched at sites of viral RNA synthesis (Brocard et al, 2018; Fritzlar et al, 2019) so it is possible that G3BP1 makes multiple contacts between the 40S subunit and viral RNA genome directly. These additional contacts, may further promote viral VPg-dependent translation and/or another aspect of the viral life cycle.…”
Section: Discussionmentioning
confidence: 99%